Usia Ibu dan Kejadian Persalinan Preterm - A'bidah Baana Syarif; Sabar Santoso; Hesty Widyasih (Jurnal Kesehatan Ibu dan Anak, 2017)
Preterm labor was a labor that occurs at 20-<37 weeks gestational age and it was one of the highest cause of infant death in theworld. Infant mortality rate in Indonesia was still very high, in Yogyakarta happened in Gunungkidul District. Maternal age factor wasone of the preterm labor problem. In 2014-2015 at Gunungkidul, the risk of maternal age increased but preterm labor decreased. Thepurpose of this study was to determine the relationship between maternal age and the incidence of preterm labor in WonosariHospital in 2016. This research was an observational study with Cross-sectional design. The research was conducted in RSUDWonosari in 2017. The technique sampling used simple random sampling and obtained 182 mothers. Data was analized using chisquaretest. The results of the study showed preterm prevalence 34,1% and aterm 65,9%. In the statistical test obtained p-value0.002 and contingency coefficient 0.227. This means that there was a correlation between mother's age and the preterm labor atWonosari Hospital in 2016 and the correlation was in a low level. As a conclusion in this study, maternal age <20 and >35 years wererisk factors that led to the incidence of preterm labor.